2018
DOI: 10.1016/j.bandl.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

When two are better than one: Bilateral mesial temporal lobe contributions associated with better vocabulary skills in children and adolescents

Abstract: This study considered the involvement of the mesial temporal lobe (MTL) in language and verbal memory functions in healthy children and adolescents. We investigated 30 healthy, right-handed children and adolescents, aged 7-16, with a fMRI language paradigm and a comprehensive cognitive test battery. We found significant MTL activations during language fMRI in all participants; 63% of them had left lateralized MTL activations, 20% exhibited right MTL lateralization, and 17% showed bilateral MTL involvement duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 103 publications
0
16
0
Order By: Relevance
“…Previous literature in healthy children and adolescents found an association between language lateralization and functioning, but conflicting findings were reported regarding the nature of this relationship: some studies found a positive correlation between language lateralization towards the left hemisphere and verbal abilities, 43, 44 whereas others reported better language performance related to less lateralization and more involvement of the contralateral hemisphere. 29, 30, 4547 The contradictory findings of these studies may be the result of different imaging methods and different tasks testing different functions. The relationship between lateralization and cognitive functioning has been reported as dependent on task demands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature in healthy children and adolescents found an association between language lateralization and functioning, but conflicting findings were reported regarding the nature of this relationship: some studies found a positive correlation between language lateralization towards the left hemisphere and verbal abilities, 43, 44 whereas others reported better language performance related to less lateralization and more involvement of the contralateral hemisphere. 29, 30, 4547 The contradictory findings of these studies may be the result of different imaging methods and different tasks testing different functions. The relationship between lateralization and cognitive functioning has been reported as dependent on task demands.…”
Section: Discussionmentioning
confidence: 99%
“…This paradigm has shown robust language lateralization in healthy children and typically involves inferior and middle frontal regions, middle and superior temporal regions, as well as mesial temporal areas including the hippocampal formation. 2630 In the auditory description definition condition, the participants listen to the definition of an object followed by a noun and are instructed to press a button each time the definition incorrectly described the noun. For instance, “A long yellow fruit is a banana.” (correct) or “Something you sit on is a spaghetti.” (incorrect).…”
Section: Methodsmentioning
confidence: 99%
“…During fMRI assessment, the German version of an auditory description definition task was administered (Bartha‐Doering, Kollndorfer, et al, 2018; Bartha‐Doering, Novak, et al, 2018; Berl et al., 2014; Sepeta et al., 2016). In the auditory description definition condition, the participants heard the definition of an object followed by a noun and were instructed to press a button each time the definition truly described the noun.…”
Section: Methodsmentioning
confidence: 99%
“…Each block lasted for 40 s and consisted of 10 sentences presented every 4 s. Total fMRI scan time was 6 min 40 s. Task performance was evaluated by the overall accuracy in the language condition and the control task separately. Detailed description of the fMRI paradigm can be found in Bartha‐Doering, Kollndorfer, et al (2018), Bartha‐Doering, Novak, et al (2018), or Bartha‐Doering et al. (2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation